COMPREHENSION STRATEGIES OF LITERARY TEXTS USED BY UNIVERSITY OF JORDAN LITERATURE STUDENTS - Yasmeen Almadani; Mohd Nazri b. Latiff Azmi; Khalid Alsmadi (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Reading plays a significant role in our daily lives. Literary readers build their worlds and expand their imagination with deviating from the literal words to create images that make sense to them in the unfamiliar places the texts describe. This study examined the most useable strategies among English language and literature students at the University of Jordan as well as whether there are significant differences between males and females in this regard. Methodology: This study employed both descriptive and quantitative approaches to collect data. The sample was selected using simple random sampling. The sample of the study was 120 EFL bachelor students divided into 60 males and 60 females from UJ. SPSS program was used in the data analysis. The research instrument was a questionnaire designed by the researcher in accordance with the study questions. SPSS social package was used to treat the collected data through multiple regression, T-test, and descriptive analyses. Result: The data analysis showed that the most usable strategies were personal growth model, cooperative learning, intensive reading, illustration, cultural model, but that doesn’t mean those are the most effective on the reading ability of literary texts. It also indicated that there are only significant differences in the use of the cultural model and the personal growth model but there aren’t any significant differences in the usage of the other mentioned strategies. Conclusion: It is recommended that the decision-makers should pay more attention to the literary texts that are provided to the university students while deciding the bachelor’s syllabus. So that they should organize literary texts in combination with the most effective reading strategies. To help them to get rid of the expected difficulties of comprehending such texts. This study contributes to supply the future bachelor syllabuses planning of English language and literature department at the University of Jordan and other universities around.